2022
DOI: 10.26525/jtfs2022.34.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Compression Effect on Several Properties of 8-Year-Old Waru Gunung (Hibiscus Macrophylllus) Wood

Abstract: The study aimed to investigate the effect of thermal compression on the properties of 8-year-old waru gunung wood. Wood specimens with the dimension of 25 mm100 mm150 mm in thickness, width and length, respectively were heated at 180 ˚C and 200 ˚C for 4 h. During the heating process, the specimens were subsequently compressed at 2.452 N mm−2 for 40 mins at each temperature. Changes in the wood chemical structure were examined using the pyrolysis-gas chromatography-mass spectrometry, the wood physical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The Implementation of girdling as a pre-harvest treatment could be an option for alleviating the inimical effect of high MCG on the thinned clonal teak stands. Girdling is a pre-harvest treatment that reduces the moisture content of the standing tree's stem as a result of photosynthates flow impediment from reaching the root system by creating inward incisions encircling the stem from the periphery to the cambium zone (Basri et al, 2015;Noel, 1970). This method has been practiced for decades as part of the teak stand management in India, Indonesia (Java), Myanmar, and Thailand (Strugnell, 1932).…”
Section: Green Moisture Content (Mcg)mentioning
confidence: 99%
See 3 more Smart Citations
“…The Implementation of girdling as a pre-harvest treatment could be an option for alleviating the inimical effect of high MCG on the thinned clonal teak stands. Girdling is a pre-harvest treatment that reduces the moisture content of the standing tree's stem as a result of photosynthates flow impediment from reaching the root system by creating inward incisions encircling the stem from the periphery to the cambium zone (Basri et al, 2015;Noel, 1970). This method has been practiced for decades as part of the teak stand management in India, Indonesia (Java), Myanmar, and Thailand (Strugnell, 1932).…”
Section: Green Moisture Content (Mcg)mentioning
confidence: 99%
“…This method has been practiced for decades as part of the teak stand management in India, Indonesia (Java), Myanmar, and Thailand (Strugnell, 1932). Previous studies reported that several months of girdling in young ages trees was effective in reducing MCG by more than 50% from the initial MCG in teak (Rini, 2013), Acacia mangium (Basri et al, 2015), and various coniferous species (Laurila et al, 2014). Therefore, it was suggested to conduct girdling as a pre-harvest treatment when practising thinning and pruning regimes on the clonal teak plantation to alleviate the adverse impact of high MCG on clonal teak wood from both silvicultural practices.…”
Section: Green Moisture Content (Mcg)mentioning
confidence: 99%
See 2 more Smart Citations
“…For these reasons, many properties of wood (such as resistance to decay) can be affected (Taylor and Cooper 2007). A longer girdling period decreases the degree of deformation during drying and also increases wood density (Basri et al 2015).…”
Section: Tree Girdling (Ring-barking)mentioning
confidence: 99%